Kettlebell swing targets semitendinosus and supine leg curl targets biceps femoris: an EMG study with rehabilitation implications. Issue 18 (26th June 2012) - Zebis, Mette Kreutzfeldt; Skotte, Jørgen; Andersen, Christoffer H; Mortensen, Peter; Petersen, Højland H; Viskær, Tine C; Jensen, Tanja L; Bencke, Jesper; Andersen, Lars L
Abstract : Background: The medial hamstring muscle has the potential to prevent excessive dynamic valgus and external rotation of the knee joint during sports. Thus, specific training targeting the medial hamstring muscle seems important to avoid knee injuries. Objective: The aim was to investigate the medial and lateral hamstring muscle activation balance during 14 selected therapeutic exercises. Study design: The study design involved single-occasion repeated measures in a randomised manner. Sixteen female elite handball and soccer players with a mean (SD) age of 23 (3) years and no previous history of knee injury participated in the present study. Electromyographic (EMG) activity of the lateral (biceps femoris – BF) and medial (semitendinosus – ST) hamstring muscle was measured during selected strengthening and balance/coordination exercises, and normalised to EMG during isometric maximal voluntary contraction (MVC). A two-way analysis of variance was performed using the mixed procedure to determine whether differences existed in normalised EMG between exercises and muscles. Results: Kettlebell swing and Romanian deadlift targeted specifically ST over BF (Δ17–22%, p<0.05) at very high levels of normalised EMG (73–115% of MVC). In contrast, the supine leg curl and hip extension specifically targeted the BF over the ST (Δ 20–23%, p<0.05) at very high levels of normalised EMG (75–87% of MVC). Conclusion: Specific therapeutic exercises targeting the hamstrings can be divided into ST dominant or BF dominant hamstring exercises. Due to distinct functions of the medial and lateral hamstring muscles, this is an important knowledge in respect to prophylactic training and physical therapist practice.